Tanggung Jawab Pejabat Pembuat Akta Tanah (PPAT) Terhadap Pendaftaran Peralihan Hak Atas Tanah Yang Menjadi Objek Sengketa - Ayu Wulan Rismayanthi, Ida (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 1 No 1 (2016)DO - 10.24843/AC.2016.v01.i01.p07, 2016)
The Land Deed Official (the PPAT) is a public official who is granted part of the authorities by the State in the implementation of land registration, by making the land certificate as the basis for land registration. The Agrarian Office may turn down the registration of the land rights in the event of any recording in the land registry books of the land rights which become the object of dispute. Based on Article 45 of the Government Regulation Number 24 of 1997 that there is a legal ambiguity on the return of the files in the form of certificate, title deed and other related documents. According to Article 55 of the Head of National Land Agency number 1 of 2006, the PPAT is personally responsible for the execution of the task and his/her authority, in every act making. There is no clear arrangement regarding the responsibility of PPAT on the registration of the conveyance of the land which becomes the object of dispute. Such provisions result in legal issues about the legal consequences and the responsibility of PPAT on the registration of the conveyance of the land which becomes the object of dispute The type of research used in this thesis is a normative legal research as the result of the presence of the ambiguity and the vacuum of norms. The legal materials were collected by the techniques of library research and the card system. The descriptive, interpretative and argumentative theories as well as associated with laws that relevant to the issues were used to analyze the legal materials. The results showed that the Agrarian Office turns down and returns the documents to the PPAT as the legal consequence of the conveyance of land which becomes the object of dispute. The legal consequences of the deed made ??before the PPAT remains authentic during a blocking of certificate. The responsibility of the PPAT is in accordance with his/her position, in keeping the deed, certificate along with the relevant documents at the time of the restitution by the Agrarian Office. PPAT shall be mandatory as an intermediary to keep the documents that are being returned at the time of confiscation by a court or at the revocation of blocking by the applicant.
Keywords: The responsibility, the PPAT, the Registration, the Conveyance, the Land Rights, the Land Dispute